2021
DOI: 10.1073/pnas.2026684118
|View full text |Cite
|
Sign up to set email alerts
|

Single-nuclear transcriptomics reveals diversity of proximal tubule cell states in a dynamic response to acute kidney injury

Abstract: Acute kidney injury (AKI), commonly caused by ischemia, sepsis, or nephrotoxic insult, is associated with increased mortality and a heightened risk of chronic kidney disease (CKD). AKI results in the dysfunction or death of proximal tubule cells (PTCs), triggering a poorly understood autologous cellular repair program. Defective repair associates with a long-term transition to CKD. We performed a mild-to-moderate ischemia–reperfusion injury (IRI) to model injury responses reflective of kidney injury in a varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
133
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 86 publications
(104 reference statements)
13
133
0
Order By: Relevance
“…All these features impact on the individual inflammatory and immune response and represent a dramatic bias, that must be taken into due account to extract the results that can allow to identify priorities in clinical decision. Consequently, standard statistical approaches are often not sufficient to control for the highly correlated structure between covariates and to account for the many potential confounding factors (Esposito 2020 ; Cippa, et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…All these features impact on the individual inflammatory and immune response and represent a dramatic bias, that must be taken into due account to extract the results that can allow to identify priorities in clinical decision. Consequently, standard statistical approaches are often not sufficient to control for the highly correlated structure between covariates and to account for the many potential confounding factors (Esposito 2020 ; Cippa, et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the associated SNPs were located in the region corresponding to the promoter of the transcript KCNIP4-IeΔII , hence the associated variants may have a regulatory role in gene expression. In a recent publication, Gerhardt et al 27 found that KCNIP4 was markedly up-regulated at the late injury stage in proximal tubule cells in an ischemia–reperfusion injury model for studying acute kidney injury (AKI). Kidney proximal tubule is particularly vulnerable to injury and maladaptive repair of injured tubules after AKI can lead to CKD 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies examined the time-course of comprehensive gene expression associated with AKI-to-CKD transition, including single-cell analyses [35][36][37][38][39]. Liu et al conducted a comprehensive gene expression analysis at multiple time points by bulk RNA-sequencing (RNA-seq) of whole kidney using a murine bilateral ischemia/reperfusion injury (IRI) model.…”
Section: Molecular Mechanisms Of Aki-to-ckd Transition: Insights From Omics Approachesmentioning
confidence: 99%